(untitled) (SETARA : Jurnal Ilmu Hukum, 2022)
This article examines legal protection concerning the recovery of court costs in industrial relations disputes after a judgment has ordered the losing party to bear those costs. The issue arises because the plaintiff usually advances the case deposit at the beginning of the proceedings, while the operative part of the judgment often only states that the losing party is ordered to pay court costs without clearly specifying to whom payment must be made. Using normative juridical research supported by a case approach, the article analyzes the legal framework of court fees under the HIR, Law Number 2 of 2004 on Industrial Relations Dispute Settlement, and relevant judicial practice. The study finds that the absence of a specific formulation regarding reimbursement of advanced court fees creates uncertainty for both the winning and losing parties and weakens legal protection in the execution stage. The article argues that clearer judicial formulations and administrative guidance are necessary so that court cost awards in industrial relations cases can be effectively enforced and fairly restored to the party that initially advanced them.